การเข้าเป็นภาคีความตกลง เพื่อส่งเสริมให้เรือประมงปฏิบัติตามมาตรการอนุรักษ์ และจัดการทรัพยากรในทะเลหลวง : ศึกษากรณีประเทศไทย - อุบลรัตน์ สู่สุข (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This thesis is aimed at studying the entry to FAO s agreement to promote compliance with international conservation and management measures by fishing vessels on the high seas whether the Thailand s potential membership will cause pros and cons. It is found that the entry to the FAO s agreement to promote compliance with international conservation and management measures by fishing vessels on the high seas will cause the cons. The writer suggests that from the time being Thailand should not enter FAO s agreement to promote compliance with international conservation and management measures by fishing vessels on the high seas according to Thailand ร national interest on the high seas is inaccurate, and the potential development of the Thai fishing fleet on the high seas is also unclear. The entry to FAO s agreement to promote compliance with international conservation and management measures by fishing vessels on the high seas establish the obligation to Thailand to perform in every binding article and Thailand is bound to implement the FAO s agreement to promote compliance with international conservation and management measures by fishing vessels on the high seas into national legislation. Thailand has to delay its entry to the Agreement, however, Thailand is capable to pick and choose particularly, the useful and appropriate provision of the Agreement to implement into national legislation.